Efektivitas Program Pelatihan Kerja dalam Pembekalan Calon Tenaga Kerja: Studi Kasus UPT Balai Latihan Kerja Pasuruan - Novitasari; Khumaidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Job Training Center is a public sector organization that has certain characteristics that are not inherent in the private sector, namely it is not oriented towards profit but towards the interests of the community. This Job Training Center functions to carry out training activities to improve and develop skills, productivity, discipline and readiness for work where the implementation prioritizes practice over theory. This study aims to determine the effectiveness of the job training program and to see how the supporting and inhibiting factors are in implementing training at the Pasuruan Job Training Center UPT. The method used is a descriptive qualitative method with observation, interview, and documentation techniques. The analysis was carried out based on 4 indicators according to Donald L Kirkpatrick, namely reactions, learning processes, behavioral changes, results and also supporting and inhibiting factors using 3 measures according to Duncan in Sa'diyah, 2020:21), namely Goal Achievement, Integrity, Adaptation. The results of the study showed that the training was quite effective in improving skills and work readiness. The facilities provided such as a) stationery b) consumption c) uniforms and d) pocket money provided by the government also support the smooth running of the training.